2012
DOI: 10.1017/s1751731111002072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlation of longevity with growth, post-mortem, docility and some morphological traits in the Pirenaica beef cattle breed

Abstract: Survival or longevity is an economically relevant trait in cattle. However, it is not currently included in cattle selection criteria because of the delayed recording of phenotypic data and the high computational demand of survival techniques under proportional hazard models. The identification of longevity-correlated traits that can be early registered in lifetime would therefore be very useful for beef cattle selection processes. The aim of this study was to estimate the genetic correlation of survival (SURV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…The posterior mean estimates of the heritabilities for the independent traits or those registered early in life (W120 and W210) ranged between 0.33 and 0.43. They are in line with previous estimates from the literature obtained in the same breed (Varona et al, 1997;Altarriba et al, 2009;Varona et al, 2012), or other beef cattle populations (Ríos-Utrera and Van Vleck, 2004;Bouquet et al, 2010). The estimates of heritabilities in the dependent traits (W210 and CW365) ranged between 0.28 (W210) to 0.38 (CW365), although they cannot be directly compared with previous estimates, because they are conditioned to the independent trait.…”
Section: Resultssupporting
confidence: 89%
“…The posterior mean estimates of the heritabilities for the independent traits or those registered early in life (W120 and W210) ranged between 0.33 and 0.43. They are in line with previous estimates from the literature obtained in the same breed (Varona et al, 1997;Altarriba et al, 2009;Varona et al, 2012), or other beef cattle populations (Ríos-Utrera and Van Vleck, 2004;Bouquet et al, 2010). The estimates of heritabilities in the dependent traits (W210 and CW365) ranged between 0.28 (W210) to 0.38 (CW365), although they cannot be directly compared with previous estimates, because they are conditioned to the independent trait.…”
Section: Resultssupporting
confidence: 89%
“…According to Varona et al. (2012), productive longevity can be defined as the number of calving per female and Banga et al. (2013) reported longevity as a trait of great economic importance in dairy and beef cattle breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy and long productive life along with good production and reproductive performance is important for successful and profitable dairy farming. According to Varona et al (2012), productive longevity can be defined as the number of calving per female and Banga et al (2013) reported longevity as a trait of great economic importance in dairy and beef cattle breeding. Gracia et al (2015) reported that direct selection for longevity led to improved health; thus, breeding for longevity results in economic benefits.…”
mentioning
confidence: 99%
“…Longevity or the age at which a cow leaves the breeding herd is a trait of great economic importance in dairy and beef cattle breeding [1]. Productive longevity can also be described as the amount of calving's per female [2]. In beef and dairy cattle, longevity plays a considerable role in the farm economy by increasing the profit realized per cow and enables greater response to selection because fewer animals exit the herd due to involuntary culling [3], a situation that provides greater selection intensity among females, and surplus heifers for sale [1].…”
Section: Introductionmentioning
confidence: 99%